Pengaruh Efektivitas Kegiatan Pembinaan Rohani oleh Penyuluh Agama Kristen Terhadap Penurunan Tingkat Stres pada Narapidana Pengedar Narkoba di Lapas Kelas IIA Sibolga - Lidwina Lestari; Melina Agustina Sipahutar; Luhut Mawardi Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the effectiveness of spiritual guidance activities conducted by Christian religious counselors on reducing stress levels among drug abuse inmates at Class IIA Sibolga Correctional Institution. This research employs a quantitative method with an inferential statistical approach. The population in this study consisted of all drug dealer inmates at Class IIA Sibolga Correctional Institution, totaling 235 individuals, while the research sample consisted of 70 respondents determined through a random sampling technique using the Slovin formula. Data collection was carried out by distributing questionnaires to the respondents. Data analysis used correlation tests and the coefficient of determination test. The results of the study show that there is a positive and significant effect between the effectiveness of spiritual guidance activities conducted by Christian religious counselors and the reduction of stress levels among drug dealer inmates at Class IIA Sibolga Correctional Institution. This is evidenced by a correlation coefficient value of 0.965, which falls into the very strong relationship category, and a significance value of 0.000 < 0.05. The results of the coefficient of determination test indicate that the effectiveness of spiritual guidance activities contributes 93.2% to the reduction of inmates’ stress levels, while the remaining percentage is influenced by other factors outside the scope of this study. Thus, it can be concluded that the more effective the spiritual guidance activities provided by Christian religious counselors, the greater the reduction in stress levels experienced by drug dealer inmates. Spiritual guidance plays an important role in helping inmates achieve inner peace, control their emotions, and improve their spiritual condition during their rehabilitation period in the correctional institution.